РАЗВИТИЕ КОММУНИКАТИВНОЙ МОБИЛЬНОСТИ КАК ОДИН ИЗ ВАЖНЕЙШИХ КОМПОНЕНТОВ УНИВЕРСАЛЬНЫХ КОМПЕТЕНЦИЙ - Хожаниязова, У. (SCIENCE and SOCIETY, 2023)
The article deals with communicative mobility as one of the components of communicative competence. Moreover, communicative mobility is considered as one of the most important components of the universal competencies of a modern specialist.
Keywords: mobility; competence; vital activity; communication; dynamism